2022
DOI: 10.1590/fst.09221
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the fruit aqueous extract of balloon pepper (Capsicum baccatum var. Pendulum) on lipid oxidation, microbiological quality and consumer acceptance of fresh pork sausage and smoked

Abstract: This study assessed the effect of different concentrations of (Capsicum baccatum var. pendulum) on lipid oxidation, microbiological and sensorial characteristics of four different formulations of fresh pork sausage and smoked (control, F1, F2, F3), with the substitution of industrial antioxidant for the natural one. Lipid oxidation values (TBARS) did not display significant differences (P>0.05) among the treatments, and at different times of analysis (storage). The only significant differences were between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Cabral et al. (2021) also reported the viability of using balloon pepper ( C. baccatum var. pendulum ) as a substitute for industrial synthetic antioxidants in fresh pork sausage and smoked ones as no significant differences were observed in lipid peroxidation and sensory qualities of the sausages.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cabral et al. (2021) also reported the viability of using balloon pepper ( C. baccatum var. pendulum ) as a substitute for industrial synthetic antioxidants in fresh pork sausage and smoked ones as no significant differences were observed in lipid peroxidation and sensory qualities of the sausages.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Olivas-Méndez et al (2022) observed that beef hamburgers treated with chipotle pepper oleoresin reduced lipid oxidation and limited the growth of microorganisms (such as Brochothrix thermosphacta, S. aureus, Salmonella spp., lactic acid bacteria, coliforms, and molds and yeasts). Cabral et al (2021) also reported the viability of using balloon pepper (C. baccatum var. pendulum) as a substitute for industrial synthetic antioxidants in fresh pork sausage and smoked ones as no significant differences were observed in lipid peroxidation and sensory qualities of the sausages.…”
Section: Novel Product Formulations Of Pepper Antioxidantsmentioning
confidence: 99%
“…Glycerol contents of CBN, CB1, CB3 and CB5 were significantly higher than that in BL (P < 0.05), and less than 0.6 g/L meeting the requirements of GB/T16289 (National Standards of the People's Republic of China, 2018). Because fatty in aged pork fat decomposed into glycerol and higher fatty acids (Cabral et al, 2022), which could lead to an increase in glycerol contents during the ageing process of Chi-aroma baijiu. With increasing year of aged pork fat, the pork fat structure was looser and easier to decompose, so the glycerol contents of Baijiu samples increasing.…”
Section: The Effect Of Aged Pork Fat On the Quality Of Chi-aroma Baijiumentioning
confidence: 99%
“…Smoked sausage products are made through the processes of raw meat processing, curing, enrobing, steaming, drying, smoking and cooling, 1 having the characteristics of western-style lowtemperature meat processing and the characteristic flavor of Chinese meat products, and are popular among consumers because of their unique aroma and taste. 2 However, harmful substances like heterocyclic amines (HAs) and N-nitrosamines (NAs) are formed easily during the thermal processing of food, and epidemiological studies have demonstrated that consuming HAs and NAs increases the risk of rectal cancer, esophageal cancer, stomach cancer and other diseases. [3][4][5] HA production in meat-based foods is influenced by a variety of factors, including physical factors such as processing temperature, time and method, and chemical factors including the content of fat and precursors.…”
Section: Introductionmentioning
confidence: 99%